Metabolic syndrome, clustering of cardiovascular risk factors and high carotid intima–media thickness in children and adolescents. Issue 4 (April 2020) - Zhao, Min; Caserta, Carmelo A.; Medeiros, Carla C.M.; López-Bermejo, Abel; Kollias, Anastasios; Zhang, Qian; Pacifico, Lucia; Reinehr, Thomas; Litwin, Mieczysław; Bassols, Judit; Romeo, Elisabetta L.; Ramos, Thacira D.A.; et al.
Abstract : Objective: The clinical utility of screening for pediatric metabolic syndrome (MetS) in children and adolescents is still controversial. We examined the performance of pediatric MetS vs. clustering of cardiovascular risk factors (which are the components of MetS) for predicting high carotid intima–media thickness (cIMT) in children and adolescents. Methods: Participants included 2427 children and adolescents aged 6–17 years from population-based studies in three countries (Brazil, China and Italy). Pediatric MetS was defined using either the modified National Cholesterol Education Program Adult Treatment Panel III criteria or the modified International Diabetes Federation criteria. Clustering of cardiovascular risk factors was calculated as the sum of five components of MetS (i.e. central obesity, elevated blood pressure, elevated triglycerides, reduced HDL-cholesterol and elevated fasting blood glucose). High cIMT was defined as cIMT at least 95th percentile values for sex and age developed from European children. Results: Presence of one, two or at least three cardiovascular risk factors (using the National Cholesterol Education Program Adult Treatment Panel III criteria), as compared with none, was associated with gradually increasing odds of high cIMT [odds ratios (95% confidence intervals): 1.60 (1.29–1.99), 2.89 (2.21–3.78) and 4.24 (2.81–6.39), respectively]. High cIMT was also associated with presence (vs. absence) of MetS (odds ratio = 2.88, 95% confidence interval = 1.95–4.26). However, clustering of cardiovascular risk factors predicted high cIMT markedly better than MetS (area under the curve of 0.66 vs. 0.54, respectively). Findings were similar using the International Diabetes Federation criteria for pediatric MetS. Conclusion: In children and adolescents, a graded score based on five cardiovascular risk factors (used to define MetS) predicted high cIMT markedly better than MetS. These findings do not support the clinical utility of MetS for screening youth at increased cardiovascular risk, as expressed in this study by high cIMT. Abstract : Supplemental Digital Content is available in the text